Dimensi Spiritualitas Ekologis Kalender Tradisional Karo - Bayu Kaesarea Ginting (Jurnal Ledalero, 2022)
Christian Church has been begun to pay attention to the local culture with involving it as the new resources of ecological spirituality in efforts of the church to study and respond the environmental crisis issues. One of elements of the local culture can be involved in that effort is Wari Sitelupuluh (WS) in Karo Culture. The research aims to find WS ecological spirituality dimensions as an alternative resource to strengthen the ecological spirituality of Karonese Church. The research used qualitative approach with enculturation theology method. The result of the research shows that WS have three applied ecological spirituality dimensions: the experience of the spirit, religious manifestation, and the expression of the spirit of the age. These three dimensions emerge two theological implications that lies WS in source of applied resistance spirituality towards anthropocentric modernconventional spirituality. The two theological implications are the sense of penggejapen (meaning: to feel) and the consciousness of rest.Keywords: Consciousness of rest, Ecological Spirituality, Penggejapen, Spirituality, Wari Sitelupuluh